2004
DOI: 10.1109/tvt.2004.823493
|View full text |Cite
|
Sign up to set email alerts
|

A Tree-Scattering Model for Improved Propagation Prediction in Urban Microcells

Abstract: Abstract-This paper presents a model for the scattering of radiowaves from the canopy of a single tree. The canopy is modeled as a cylindrical volume containing randomly distributed and oriented cylinders, representing the branches, and thin disks, representing the leaves. A simple expression for the incoherent scattered field outside the canopy is obtained using Twersky's multiple scattering theory. This expression is shown to agree well with results of scattering measurements on a live tree typical of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 21 publications
(41 reference statements)
4
89
0
Order By: Relevance
“…Each set has 10 samples collected from same plant. Each set was formulated and combined to obtain one equation as below in Equation (6) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each set has 10 samples collected from same plant. Each set was formulated and combined to obtain one equation as below in Equation (6) …”
Section: Resultsmentioning
confidence: 99%
“…The physical optic parameters were obtained for X band before, and dielectric constants of tropical leaves were measured and calculated in the literature at X band. Sarabandi [6] and Senior [7] showed that a resistive sheet constitutes an effective model of a leaf.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the use of MST introduces enormous requirements in terms of computation time and the software implementation complexity [4][5][6]. Recently, the authors have developed in [7] a new model addressing scattering from tree canopies which significantly lowers the corresponding requirements by replacing MST coherent field calculations by utilizing the physical optics (PO) approach based on [8].…”
Section: Of 16mentioning
confidence: 99%
“…The reason is that, in this case, the corresponding tree canopy can be spatially sampled by voxels of sides exceeding half the wavelength [6], thus, significantly decreasing the computation time. We should note, however, that shadowing behind a tree canopy results only from the coherent field [4][5][6].…”
Section: Multiple Scattering Theory (Mst)mentioning
confidence: 99%
See 1 more Smart Citation